Psychometric Properties of Interpersonal Support Evaluation List (ISEL) In the Indonesian Cultural Context - Peristianto, Sheilla Varadhila; Ramli, Zaskia Andini; Khadri, Mohd Wafiy Akmal Ahmad; Wider, Walton (Faculty of Psychology, Universitas Diponegoro, 2026)
Background: Social support is a key psychological construct widely examined in various research contexts. Cohen’s theory of social support underlies the development of the Interpersonal Support Evaluation List (ISEL-40), which measures perceived social support. Although the ISEL-40 has been adapted into several languages, empirical validation of its full version in the Indonesian context remains limited and methodologically constrained in prior studies.Purpose: This study aims to illuminate the psychometric properties of the Indonesian version of the ISEL-40.Method: This study involved 600 respondents from the Central Java Province and the Special Region of Yogyakarta, language-culture adjustments, and reliability analysis of Cronbach's Alpha, Confirmatory Factor Analysis (CFA), and Multidimensional Scaling (MDS).Findings: The results indicate that the Indonesian ISEL-28 demonstrates adequate reliability and construct validity. The overall Cronbach’s alpha was .910, while CFA results showed acceptable model fit (RMSEA = .079; RMR = .050).Implication: The validated Indonesian ISEL-28 supports culturally relevant research and practice and provides a foundation for future cross-cultural studies in Indonesia.